Reactions of 2,2,6-Trimethyl-1,3-dioxin-4-one with the Aryl Aldimines Prepared from Thiophene-2-carbaldehyde - Koser, Ilayda; Ocal, Nuket; Erden, Ihsan (WILEY, 2017)
The reactions of aryl aldimines derived from thiophene-2-carbaldehyde (5-9) with 2,2,6-trimethyl-1,3-dioxin-4-one (1) were investigated. The new 1,3-oxazin-4-ones and thienylidene acetoacetamides were obtained in good yields. The synthetic utility of the latter via an intramolecular tandem Friedel-Crafts alkylation-acylation to give tetracyclic heterocyclic rings was also explored.
Keywords: COMPLEXES; IMINES; Chemistry